Study of the asynchronous traction drive's operating modes by computer simulation. Part 2: simulation results and analysis - Pavel KOLPAHCHYAN; Alexander ZARIFYAN Jr (Transport Problems, 2015)
The problem arising at the design of electric locomotives with asynchronous traction drive are considered. The electrical scheme provides the possibility of individual (by axle) control of traction motors. This allows realizing the operational discon-nection/connection of one or more axles in the automatic mode, with account of actual load. In Part 1 of this paper, the complex computer model based on the representation of AC traction drive as controlled electromechanical system was developed. The description of methods applied in modeling of traction drive elements (traction motors, power converters, control systems), as well as of mechanical part and of "wheel-rail" contact, was given. In Part 2, the results of dynamic electromechanical processes modeling in various modes of electric locomotive operation (start and acceleration, traction regime in straight and curve railway sections, wheel-slide protection, etc.) are presented. In perspective, based on the developed model, the evaluation of locomotive's energy efficiency at the realization of various control algorithms must be obtained.